ความหลากหลายของสาหร่ายทนร้อนในลำธารน้ำพุร้อนบางแห่งในจังหวัดเชียงใหม่ จังหวัดเชียงราย และจังหวัดแม่ฮ่องสอน - อังคณา คณีกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
Diversity of thermophilic algae was investigated in 7 hot springs: Sankampang, Phang, Rungaroon, Tepanom and Pongdeuad in Chiangmai Province; Pongnamron Maechan in Chiangrai Province and Muangpang in Mae Hong Son Province where maximum temperature is above 90 ํC in October 1999 and April 2000. There are 62 species, belonging to 23 species of blue green algae, 18 species of green algae and 21 species of diatoms. The dominant species are Oscillatoria agardhii Gomont., Oscillatoria angusta Koppe., Oscillatoria boryana Bory ex Gomont., Synechococcus aeruginosus Nag., Diatomella balfouriana Grev., Diatomella parva Manguin and Surirella linearis W. Sm. According to the available taxonomic literature, 18 species are possible new records to Thailand whereas 1 Cosmarium sp. and 9 varieties of algae are expected to be new species and new variety, respectively. Most of algae are unicellular and found in open area where temperature is 40-69 ํC and pH is 8.7-9.9. Furthermore, of all algae studied 18 species grow in wide range of temperature (from 40 ํC to above 90 ํC). Of which, 12 species are hyperthemophile (above 80 ํC). All of voucher specimens were preserved with 4% formaldehyde solution and collected at Professor Kasin Suvatabundhu Herbarium, Department of Botany, Faculty of Science, Chulalongkorn University (BCU). Description of all families genera and species, key to families, genera and species, ecology, distribution and photographs were also made.